Level of Awareness Among Elderly Persons and Hinderances to Unconditional Cash Transfer Accessibility. A Case Study of Tharaka Nithi County in Kenya (Global Journal of Human-Social Science, 2022)
There are notable cases in other developing countries where unconditional cash transfer programs have failed due to inadequate information of unconditional cash transfer. Within the context of these arguments, the purpose of the study is to establish the level of awareness of unconditional cash transfer among elderly persons in Tharaka Ninthi County in Kenya. The study adopted a descriptive survey research design. Target population was 1003 beneficiaries and employees of Ministry of Labour, Social Security and Services (Department of Social Development) where a sample of 102 respondents was drawn. The study employed simple random sampling to select the respondents who participated in the study. The study used questionnaires and interviews as the main data collection instruments. The study used test-retest to establish the reliability of each section of the questionnaires. The data collected was analyzed using descriptive and inferential statistics. Data from the interviews were analysed using scientific packages for social sciences and presented using thematic analysis.
Keywords: ministry of labour; social security and services (department of social development)